Prevention of Norovirus Contamination as an Effort to Reduce the Incidence of Diarrhea in Pondok Pesantren Putri Wahid Hasyim Bangil - Rusdi, Warda Elmaida; Farindra, Irmawan; Zuwariyah, Nur; Adriansyah, Agus Aan; Farakhin, Noer (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Boarding schools are vulnerable places because many students living in one environment will increase the spread of Norovirus. Where this disease can cause diarrhea and the incidence of diarrhea is very common in the boarding school environment. Therefore, this activity aims to improve personal hygiene habits as a form of controlling the incidence of diarrhea caused by Norovirus. Methods: This community service which was held in June 2023 was attended by 40 participants from PP Putri Wahid Hasyim Bangil. Activities carried out in the form of providing education, character building of santri and administrators with health games and distribution of pretests and postests. This study was conducted descriptively observational to see the response of participants by looking at the enthusiasm and increase in knowledge of participants by using Wilcoxon test analysis. Results: The results showed a p-value of 0.005. Because the significance value shows p < 0.005, it can be concluded that